6-Gingerol Activates PI3K/Akt and Inhibits Apoptosis to Attenuate Myocardial Ischemia/Reperfusion Injury - Lv, Xiangwei (Evid Based Complement Alternat Med, 2018)
6-Gingerol (6-G) is known to alleviate myocardial ischemia/reperfusion injury. However, the underlying molecular mechanisms of 6-G myocardial protection are not known. In this study, the protective effect of 6-G on ischemia/reperfusion (I/R) damage and whether such a mechanism was related to apoptosis inhibition and activation of phosphoinositide 3-kinases (PI3K)/serine/threonine kinase (Akt) signaling pathway were investigated. Rats were subjected to I/R in the presence or absence of 6-G and the changes of cardiac function, infarct size and histopathological changes, and the levels of cardiac troponin T, creatine kinase-MB, and myocardial apoptosis were examined. The expression of caspase-3, PI3K, p-Akt, and Akt was also determined. We found that 6-G (6 mg/kg) pretreatment significantly improved heart function and ameliorated infarct size and histopathological changes and cardiac troponin T and creatine kinase-MB levels induced by I/R. Moreover, pretreatment with 6-G significantly inhibited myocardial apoptosis and caspase-3 activation induced by I/R. 6-G also upregulated expression of PI3K, p-Akt, and Akt in myocardial tissues. Taken together, these findings suggest that 6-G inhibits apoptosis and activates PI3K/Akt signaling in response to myocardial I/R injury as a possible mechanism to attenuate I/R-induced injury in heart. These results might be important for developing novel strategies for preventing myocardial I/R injury.